Neuro-Fuzzy Control of Single Machine Infinite Bus Power System - Ali, Abduladhem A.; Abbas, Abbas H.; Jassim, Rasheed S. (Basrah Journal for Engineering Sciences, 2010)
The excitation and governing control of generator play an important role in improving the dynamic and transient stability of power system. Typically the excitation control and governing control are designed independently. This paper, presented Neuro-Fu;,.zy methods for the excitation and governing control . Neuro-Fuz.zy system is applied to generate two compensating signals to modify the controls dwing system disturbances. A single machine to infinite bus (SMIB) system is applied in simulation. The MATLAB SIMULIK and S-function technique is used to simulate the system and controllers